Federal Income Tax Handbook/Federal Taxes on Estates, Gifts and Trusts (Book). - Smith, Dan Throop (The Accounting Review, 1939)
Reviews the books "Federal Income Tax Handbook, 1938-39," by Robert H.Montgomery and "Federal Taxes on Estates, Gifts and Trusts, 1938-39," by Robert H.Montgomery.